The relationship between psychological energy levels and physical fitness among senior football players: A field study of teams in the Bouira region. - hadj ahmed, Mourad (sports creativity, 2025)
This study aimed to identify the nature of the relationship between psychological energy levels and physical fitness levels among senior football players in the Bouira province, using the variables of sports experience and level of competition. It also sought to determine the impact of certain psychological skills on psychological energy. The research sample consisted of 14 players, selected purposively and equally distributed across four teams: Wifaq Sour El Ghozlane (Inter-Regional Division, Central), El Khadriya (Regional Division 1, Central), Chaabia Bouira (Regional Division 2, Central), and Hamzaouia Ain Bessam (Honor Division, Bouira). All these teams were selected from within the Bouira province. The researcher employed a descriptive survey methodology, subjecting the skill-based research sample to a series of physical tests using a six-point psychological fluency scale. Means, standard deviations, the coefficient of correlation, and Pearson's correlation coefficient were used to calculate the results. One of the results of this study is the confirmation of the positive role that athletic experience plays in enhancing the relationship between psychological energy and physical attributes in athletes. This is achieved through effective management of positive and negative energy sources, which allows them to improve their physical fitness. The study also highlights the negative role of high levels of experience, which can create significant psychological pressure on athletes, leading to a decline in their physical fitness. This underscores the necessity of psychological preparation for elite athletes. Therefore, the researcher recommends that training programs focusing on physical, technical, and tactical aspects be complemented by psychological skills training programs prepared by a sports psychologist in collaboration with the team's technical staff. Furthermore, the researcher recommends conducting training courses for team coaches at physical education and sports institutes to highlight the importance of psychological energy and its role in improving team performance. Finally, the study suggests awareness campaigns and theoretical lectures for athletes addressing the role of psychological energy in enhancing their physical and technical performance, as well as emphasizing the need for a sports psychologist to be present at training facilities. Their training and official competitions necessitate that teams be supported by a specialist in sports psychology, preferably someone with sports experience, to bolster the team's technical staff. [Intervention:]